Stellar feedback from black-hole high-mass X-ray binaries in galaxy formation models - Artale, Maria Celeste (2014)
In recent years, many works have suggested the role of black-hole high-mass X-ray binaries (BH-HMXB) as potential sources of heating and re-ionization in the interstellar and intergalactic medium. Furthermore, because of the suggested increase of their production rate and X-ray luminosity with decreasing metallicity, BH-HMXBs could be relevant to explain the thermal and ionization history of the Universe at its early stages. As observations indicate, a meaningful amount of the energy released by these sources could be deposited in the local interstellar medium, suggesting that BH-HMXB could modify star forming regions on the host galaxy. In this work, we study the kinetic BH-HMXB feedback using hydrodynamical cosmological simulations which also include SNe feedback. Our preliminary results suggest that BH-HMBXs feedback is not efficient at modifying the star formation activity. However, due the complexity of the problem and the wide dynamical range needed to describe properly different physical events, there are still different schemes to explore. In the future, we will study the role of BH-HMXBs in high numerical resolution simulations at high redshifts, and how the energy is released into the interstellar medium.